2019
DOI: 10.1002/fsn3.1247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermentation and dry roasting on the nutritional quality and sensory attributes of quinoa

Abstract: BackgroundQuinoa is a pseudocereal with relatively high content of proteins and minerals that also contains mineral inhibitors such as phytate. The aim of the present study was to evaluate lactic acid fermentation and dry roasting on the nutritional quality and sensory attributes of quinoa. Various processes were evaluated, and quinoa grains were dry‐roasted, milled, and fermented, either with or without the addition of wheat phytase or activated quinoa phytase (added as back‐slop starter), for 10 hr. In other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Furthermore, the highest phytic acid reduction (98%) was observed after fermentation of the germinated flour [82]. Moreover, Castro-Alba et al [83] recently reported that fermentation (4 or 10 h, at 30 • C) of milled quinoa seeds using L. plantarum 299v reduced the phytic acid significantly and improved the bioavailability of minerals such as Ca, Fe, and Zn [83]. In another previous study, the effect of natural sourdough fermentation of wheat showed a much better improvement of copper and magnesium absorption in comparison to nonfermented wheat flour, using male Wistar rats.…”
Section: Influence Of Fermentation On Micronutrients Bioavailability mentioning
confidence: 92%
“…Furthermore, the highest phytic acid reduction (98%) was observed after fermentation of the germinated flour [82]. Moreover, Castro-Alba et al [83] recently reported that fermentation (4 or 10 h, at 30 • C) of milled quinoa seeds using L. plantarum 299v reduced the phytic acid significantly and improved the bioavailability of minerals such as Ca, Fe, and Zn [83]. In another previous study, the effect of natural sourdough fermentation of wheat showed a much better improvement of copper and magnesium absorption in comparison to nonfermented wheat flour, using male Wistar rats.…”
Section: Influence Of Fermentation On Micronutrients Bioavailability mentioning
confidence: 92%
“…For example, in a study surveying the effect of fermentation (16−18 h, 30 • C) with commercial L. plantarum starter, it was observed that the amount of soluble Fe in quinoa suspension was significantly increased in comparison to nonfermented suspension, while the content of phytic acid was significantly decreased [145]. Furthermore, fermentation (4, 10, or 48 h, 30 • C) of milled quinoa seeds with L. plantarum 299v has shown good efficiency in reducing phytic acid and a moderate capability to improve estimated Zn, Fe, and Ca availability [144]. These improvements were apparent already after 4 h [144].…”
Section: Applying Fermentation To Boost the Nutritional Quality Of Cementioning
confidence: 97%
“…Because fermentation is a traditional way to process cereals for improvements in nutritional and sensory quality, it is also more and more frequently applied to process pseudocereal quinoa [30,[141][142][143][144][145]. Fermentations with L. plantarum strains have been found to increase Fe, Zn, and Ca solubility and to reduce phytic acid.…”
Section: Applying Fermentation To Boost the Nutritional Quality Of Cementioning
confidence: 99%
See 2 more Smart Citations